Creating and analysing the Digital Terrain Model of the Slivovo area using QGIS software. Issue 3 (3rd July 2017) - Maliqi, Edon; Penev, Petar; Kelmendi, Faik
Abstract: The aim of the paper is developing the Digital Terrain Model (DTM in the further text) through QGIS software. In order to accomplish intention of the paper will test some of the methods and techniques that are widely known in nowadays and those are supported by QGIS software – an open source software. And those methods named TIN and GRID. For showing complexity on the study area will analyse some features or characteristics of terrain in the created DTM. All of these methods and techniques will be applied in QGIS. In general, the QGIS software has rich methodology for creation, intepretation, visualization and analysing the geo-spatial data and the DTM in particular.